Fatores de influência nas características físico-químicas e minerais da casca do maracujá amarelo e seu aproveitamento na elaboração de doce - Reolon, Carla Aparecida (2008)
The fruit juice industry uses around 30% of the total mass of fruits that are processed and the rest is regarded as industrial waste. This waste can be used for human consumption aiming to use for other purposes. Thus, this work was aimed at: 1 - To evaluate the effect of maturity stage of the yellow passion fruit on the physical, chemical and mineral characteristics of their shell, 2 - To evaluate the effect of storage of the yellow passion fruit shell on their physico-chemical and minerals characteristics, 3 - development and evaluation of sensory acceptability of the candy syrup of the yellow passion fruit shell, with the addition of its juice. It was used to completely randomized design with four repetitions for the treatment of stages of maturation and five repetitions for the treatment of storage. Were evaluated the contents of ash, pectin, total and reducing sugar, protein, fat, dry mater and loss of weight. The evaluates minerals parameters were: calcium, copper, iron, manganese, potassium, magnesium, zinc, phosphorus. Color analysis for the treatment of shell storage was held.The acceptance analysis was based on the study of aroma, flavour, overall impression and purchase intent using structured scales and participation of 50 judges not trained. Each judge received a questionnaire containing hedônica structured scale of nine points covering answers ranging from ''1 - most disliked " at ''9 - liked very much''. In purchase intent analysis to was used structured three-point scale, with "1 - certainly not buy" and "3 - certainly buy". Throughout the study was used completely randomized design. The results were submitted to the analysis of variance and the significant effects was applied to the Tukey test and the regression analyses. The advance of maturity resulted in the reduction of the contents of protein, reducing sugar, total pectin and ash, showing that the best use of the shell, to use Phitoterapic, occurs when the fruit is a green stadium, where the pectin content is higher. The low lipids content of the shell indicates a final product of low calorie, when used as phitoterapic and when consumed in full form. There was no effect of maturation stages in the minerals content. The yellow passion fruit shell is good source of manganese, followed by iron, zinc and copper. In other nutrients, the shell this fruit has proved inadequate and low supply for a diet. As for the storage of the shell, there were effective decreases in the contents of protein, lipids, total sugar, ash and pectins during the period of storage. With the exception of copper, manganese and calcium, for other minerals was effective reductions in levels of zinc, magnesium, potassium, phosphorus and iron during storage of the fruit shell. The color analysis indicated the occurrence of browning of the shell with the advance of storage time. The storage damaged the nutritional quality and appearance of shell. As the acceptance analysis of the shell candy syrup, there was good acceptance by consumers, because more than 70% of them attributed notes above 7 in all candys. Among the treatments tested, the candy with the addition of 4% of the fruit juice was the most accepted by judges in all attributes (aroma, flavor, overall impression and purchase intent). The use of the shell of the yellow passion fruit in the development of a candy syrup is an excellent choice of value aggregation